2015
DOI: 10.5433/1679-0359.2015v36n6supl2p4225
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of detomidine in combination with saline, morphine or methadone in horses submitted to experimental oral stimuli

Abstract: A comparison of detomidine in combination with saline, morphine or methadone in horses submitted to experimental oral stimuli Comparação entre a associação da detomidina à solução salina, à morfina ou à metadona em cavalos submetidos aos estímulos experimentais na cavidade oral AbstractThis study aimed to compare the sedative and cardiopulmonary effects of detomidine in combination with saline, morphine or methadone and to determine whether the addition of these opioids increases the degree of sedation in hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…The literature shows other studies assessing the association of α-2 agonists with other drugs to perform dental procedures, in which the association between 10 µg kg −1 of detomidine and morphine or methadone, both at a dose of 0.1 mg kg −1 , promoted a reduction of 44 and 41% in head height, respectively. This reduction was lower than that observed when using detomidine alone, which presented a 70% reduction (Guilhen et al, 2015), a value similar to that found in the present study for GD and GDL. The authors used the same assessment scale as the present study, with lower scores than the basal from 5 to 30 min after treatment administration, with no differences between scores in relation to basal after 30 minutes (Guilhen et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The literature shows other studies assessing the association of α-2 agonists with other drugs to perform dental procedures, in which the association between 10 µg kg −1 of detomidine and morphine or methadone, both at a dose of 0.1 mg kg −1 , promoted a reduction of 44 and 41% in head height, respectively. This reduction was lower than that observed when using detomidine alone, which presented a 70% reduction (Guilhen et al, 2015), a value similar to that found in the present study for GD and GDL. The authors used the same assessment scale as the present study, with lower scores than the basal from 5 to 30 min after treatment administration, with no differences between scores in relation to basal after 30 minutes (Guilhen et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…This reduction was lower than that observed when using detomidine alone, which presented a 70% reduction (Guilhen et al, 2015), a value similar to that found in the present study for GD and GDL. The authors used the same assessment scale as the present study, with lower scores than the basal from 5 to 30 min after treatment administration, with no differences between scores in relation to basal after 30 minutes (Guilhen et al, 2015). Such difference can be attributed to the form of administration, as the previous study used single bolus and the present study administered drugs in continuous infusion, with no reduction in sedation scores over time.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations